PERLINDUNGAN HUKUM DALAM KASUS KEKERASAN DAN PERBUDAKAN MANUSIA - Dianita Putri Oktavia Damayanti; Frans Simangunsong (Gapenas Publisher, 2022)
Human rights are legal instrument that must be respected, upheld, and protected by the state. Within human rights itself, there are rights to life, the right not to be tortured, and the right not to be enslaved. With the regulation on Human Rights and the Crime of Trafficking in Persons, everyone gets legal protection from acts that degrade human dignity. The consequences of criminal penalties for the perpetrators absolutely must be strictly enforced against those who have injured humanity